Pan-Cancer Analysis of Atrial-Fibrillation-Related Innate Immunity Gene ANXA4 - Yan, Tao; Zhu, Shijie; Shi, Yu; Xie, Changming; Zhu, Miao; Zhang, Yangyang; Wang, Chunsheng; Guo, Changfa (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) is the most common tachyarrhythmia around the world. Cancer is one of the main causes of death worldwide. A recent study demonstrated that cancer was associated with an increased incidence of AF. In the present study, we aimed to explore possible mechanisms and potential common therapeutic targets between AF and cancer. Methods: Differentially expressed proteins between AF and sinus rhythm were identified utilizing proteomics analysis. Weighted gene correlation network analysis was applied to cluster proteins into different modules and investigate associations between modules and AF. Hub immune-related genes were selected via InnateDB database and verified using qRT-PCR. RNA sequencing and clinical data of 33 different cancer types were achieved from The Cancer Genome Atlas (TCGA). The correlations between ANXA4 expression and the prognosis were calculated utilizing Cox regression analysis and Kaplan-Meier survival analysis. Spearman's rank correlation test was used to assess associations between ANXA4 and immune infiltration and DNA methylation. Enrichment analysis was performed through gene ontology and gene set enrichment analysis (GSEA). Results:ANXA4 was identified as hub immune-related gene between AF and sinus rhythm. Expression levels of ANXA4 increased in diverse cancer types. Survival analysis suggested prognostic significance of ANXA4 expression levels in various cancer types. Immune correlation analysis indicated that ANXA4 expression levels were associated with tumor immune infiltration in most cancer types. ANXA4 might influence the efficacy of immunotherapy via tumor burden and microsatellite instability. GSEA results indicated that high ANXA4 expression groups were mainly enriched in peroxisome, bile acid biosynthesis, and p53 pathway. Conclusion:ANXA4 was identified as a hub immune-related gene in AF, which has never been reported. Pan-cancer analysis indicated its potential as a novel clinical prognostic marker and therapeutic target in diverse cancer types. ANXA4 might play crucial roles in AF and cancer, and targeted therapy for ANXA4 might reduce the incidence of AF in cancer patients.